Oxytocin Attenuates Atherosclerosis and Adipose Tissue Inflammation in Socially Isolated ApoE(−/−) Mice - Nation, Daniel A. (Psychosom Med, 2010)
OBJECTIVE: To determine the effect of exogenous oxytocin (OT) administration on inflammation and atherosclerosis in socially isolated apoE(−/−) mice. Hyperlipidemic animals housed in isolated or stressful social environments display more extensive atherosclerosis than those in an affiliative social environment. The neurohypophyseal peptide OT may be involved in both affiliative social behavior and cardiovascular homeostasis, suggesting a role in mediating the benefits of positive social interactions on atherosclerosis. METHODS: A total of 43, 12-week-old, apoE(−/−) mice were surgically implanted with osmotic minipumps containing OT (n = 23) or vehicle (n = 20). Blood samples were taken at baseline and after 6 weeks and 12 weeks of treatment. After 12 weeks of treatment, animals were killed, and samples of adipose tissue were dissected from a subset of OT-treated (n = 12) and vehicle-treated (n = 12) animals and incubated in culture media for 6 hours. Media samples were analyzed for interleukin (IL)-6 concentration corrected by sample dry weight. Aortas were dissected, formalin-fixed, and stained with oil-red O for en face quantification of lesion area. t tests were used to compare group means on measures of percent lesion area and IL-6 concentrations. RESULTS: There were no group differences in plasma lipids. Adipose tissue samples taken from OT-treated animals secreted significantly less IL-6 over 6 hours (p < .01). OT-treated animals displayed significantly less atherosclerosis in the thoracic aorta (p < .05). CONCLUSIONS: These results indicate that peripheral OT administration can inhibit atherosclerotic lesion development and adipose tissue inflammation, suggesting a potential role for this neuropeptide in mediating the benefits of stable group housing on atherosclerosis.